Psychometric properties of a Chinese version of the Constructivist Learning Environment Survey among secondary-school students in Hong Kong - Kwan, Yee Wan (Learning Environments Research, 2020)
The study examined the factor structure, reliability and validity of a Chinese version of the Constructivist Learning Environment Survey (C-CLES), an instrument for assessing students’ perceptions of the extent of constructivist approaches prevalent in classrooms. A convenience sample of 967 students in Secondary Three (Grade 9) in Hong Kong participated in this study by completing a self-administered questionnaire in their class time. Exploratory and confirmatory factor analyses supported the hypothesised factor structure, indicating five theoretical constructivist environment dimensions that showed goodness-of-fit to 25 items: Personal Relevance, Uncertainty, Critical Voice, Shared Control, and Student Negotiation. Criterion-related validity, involving evidence based on relations to other variables, was assessed by correlations between the constructivist environment dimensions and cognitive strategies and academic ability. Most correlations were statistically significant and in the positive direction. The C-CLES with 25 items provides a useful measure for educational practice and research among school students.
Keywords: Cognitive outcomes; Constructivist learning environment; Secondary schools; Validation

Inclusive Education Teachers—Strategies of Working Collaboratively With Parents of Children With Special Educational Needs in Macau - Ng, Shun Wing; Kwan, Yee Wan (International Journal of Educational Reform, 2020)
Education for learners with special education needs has become one of the major concerns of education policies in every corner of the world. In Macau, however, the transformation of schools into inclusive environments is reported to be slow because many teachers in Macau have not accepted the key values of inclusive education and possess little knowledge of their responsibilities as inclusive education teachers. Despite being nonempirical, the aim of this article is twofold: to inform inclusive education teachers, especially those in Macau and other developing regions, of the necessary knowledge, skills and strategies of working collaboratively with parents of children with SEN and provide policy makers concerned with practical ideas of designing effective professional development programmes for teachers working in the inclusive environment. The ultimate aim is to ensure that children with SEN benefit from an education process that includes quality learning opportunities.

How Schools in Macau Create Intellectual Capital for Development - Ng, Shun-wing; Kwan, Yee-wan (Managing School Intellectual Capital for Strategic Development, 2022)
This chapter describes how intellectual capital comprising human capital, structural capital, and relational capital are being created for school development and quality assurance in Macau. Macau has aimed to catch up with the global education reform by subsidising majorities of the non-tertiary sectors and promulgating Decree Laws regarding education policies and development. Despite the significance of the intangible assets of the intellectual capital, the chapter also attempts to analyse the issues and challenges towards the management of intellectual capital emerging simultaneously in the transition process in the educational context of Macau. It suggests capitalising on the accumulated school knowledge for school effectiveness. This chapter depicts the chronological development of Macau's education reform by analysing how Macau has attempted to emancipate its education institutions from the period of quasi-closed system to that of the open system by creating different types of intellectual capital in school. It discusses the emerging issues and challenges simultaneously in the transition process of educational development in Macau, namely before and after returning its sovereignty to the Chinese government.

Enhancing Student Learning and Teacher Development: Does “Assessment for Learning” Matter? - Ng, Shun Wing; Kwan, Yee Wan; Huey Lei, Ka Hio (International Journal of Educational Reform, 2020)
This paper aims to report a case study of exploring the effect of ?assessment for learning? on improving student learning and facilitating teachers? professional development in the examination-oriented context of Hong Kong. By adopting Variation Theory of the Lesson Study approach, data were collected through pre- and post-tests, interviews with students and teacher participants and observation field-notes in order to help diagnose students? learning difficulties and provide evidence for teachers to refine their teaching strategies to enhance students? learning effectiveness. The students? improvement in learning performance informed the teacher participants of the usefulness of ?assessment for learning? in the classroom.